Correlation between Measurement of Lung Diffusion Capacity Using Single Breath Methods (DLCO-SB) and COPD Group in Persahabatan Hospital Jakarta - Efriadi Ismail; Faisal Yunus; Triya Damayanti (Jurnal Respirologi Indonesia, 2021)
Background: This was a preliminary study to measure DLCO-SB on COPD patients in Persahabatan Hospital to understand the prevalence of DLCO reduction among COPD patients.Methods: This was a cross sectional study of COPD patients who attended COPD-Asthma clinic in Persahabatan Hospital Jakarta. Spirometry and DLCO-SB were performed consecutively during May–July 2015.  Comorbidities were also recorded.Results: Spirometry and DLCO-SB measurements were conducted on 65 COPD subjects of which 10.8% subjects were in COPD Group A, 29.2% Group B, 32.3% Group C and 27.7% Group D. The mean age was 64.15; mean FEV1% was 46.05%, mean DLCO measured was 19.42 ml/min/mmHg and the mean DLCO% was 72.00%. The proportion of DLCO decline among COPD patients was 56.92%.  There were significant correlations between COPD group, GOLD COPD grade, FEV1, BMI and comorbidities with the DLCO value results. There were no significant correlation between DLCO value with sex, age, smoking history, Brinkmann Index, obstructive-restrictive criteria, comorbidities and length of COPD period. Conclusion: The proportion of DLCO decline among COPD patients was 56.92%. There were significant correlations between COPD group, GOLD COPD grade, FEV1, BMI and previous TB history with the results of DLCO.